Islamic Education Planning: The Concept of Educational Management in Madrasah - Nurjali, Nurjali (Zabags International Journal of Education, 2024)
This study aims to understand the important role of educational management planning in Madrasah in achieving national education goals. The methodology used is a literature study with a qualitative approach, collecting data from references to books, journals, archives, and related documents. The results of the study indicate that educational management planning has a significant influence on the effectiveness of other management functions, such as organizing, motivating, and supervising. In conclusion, good planning allows educational institutions to direct strategic steps towards achieving long-term visions effectively and efficiently. The novelty of this study lies in the in-depth analysis of the application of educational philosophy in educational management planning in Madrasah, as well as its influence on the national education system. The recommendation from this study is the need to increase awareness among education stakeholders to adopt a more responsive and innovative planning model to face future educational challenges.